2013
DOI: 10.5194/bg-10-3615-2013
|View full text |Cite
|
Sign up to set email alerts
|

Emission of atmospherically significant halocarbons by naturally occurring and farmed tropical macroalgae

Abstract: Current estimates of global halocarbon emissions highlight the tropical coastal environment as an important source of very short-lived (VSL) biogenic halocarbons to the troposphere and stratosphere, due to a combination of assumed high primary productivity in tropical coastal waters and the prevalence of deep convective transport, potentially capable of rapidly lifting surface emissions to the upper troposphere/lower stratosphere. However, despite this perceived importance, direct measurements of tropical coas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
93
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(103 citation statements)
references
References 76 publications
7
93
3
Order By: Relevance
“…It may be related to changes in the activity of bromoperoxidases, a decreasing production of PHM precursors, reduced oxidative stress, or the build-up of substrates that can be halogenated but compete with PHM formation. However, our results corroborate those of Leedham et al, [25] who reported 3-to 10-fold higher production rates from 4-h incubations as compared with 24-h incubations.…”
Section: Production Ratessupporting
confidence: 93%
See 3 more Smart Citations
“…It may be related to changes in the activity of bromoperoxidases, a decreasing production of PHM precursors, reduced oxidative stress, or the build-up of substrates that can be halogenated but compete with PHM formation. However, our results corroborate those of Leedham et al, [25] who reported 3-to 10-fold higher production rates from 4-h incubations as compared with 24-h incubations.…”
Section: Production Ratessupporting
confidence: 93%
“…Other factors that may account for the different production rates are the pH of the seawater (IFBM, 8.1; IOW, ,7), the sampling location and the sampling season. However, in summary, the production rates and their variability found here (Tables S1, S4, S5) fit in the range of previous studies, [25] with the IOW production rates being at the lower end and the IFBM production rates being in the middle to upper range.…”
Section: Production Ratessupporting
confidence: 87%
See 2 more Smart Citations
“…Biogenic emissions from the oceans have been identified as one of the main natural sources where organisms such as macroalgae (seaweeds) and microalgae (phytoplankton) can release large quantities of halocarbon gases into the atmosphere (Sturges et al, 1993;Moore et al, 1996;Laturnus and Adams, 1998). Previous ship and coastal measurements have collected bromocarbon data for many different global regions, summarised in Montzka et al (2011).…”
Section: Introductionmentioning
confidence: 99%